Callus Induction from Explants of Eurycoma Longifolia Jack (Tongkat Ali) and the Production of 9- Methoxycanthin-6-One from the Induced Callus - Noormi, Rosli (2005)
A study was carried out to determine 9-methoxycanthin-6-one distribution in intact plants and callus cultures of Eurycorna longfolia Jack. Qualitative analysis using TLC revealed that 9-methoxycanthin-6-one was present in leaf, petiole, stem, rachis, tap root, fibrous root, cotyledon and zygotic embryo of intact plant. The quantitative analysis using HPLC showed that the highest concentration of 9-methoxycanthin-6-one content was found in tap root. It was 4.10 mg/g DW tissues. 9-methoxycanthin-6-one was also present in callus tissues derived from different explants. The highest concentration was detected in fibrous root-derived callus (7.12 mg/g DW tissues). From the comparison between the data of callus tissues and intact plant parts, higher concentration of 9-methoxycanthin-6-one, more than 73.7 % was detected in callus tissues. The ability of the callus to produce 9-methoxycanthin-6-one in different types of basal media (Murashige and Skoog, Gamborg, Schenk and Hildebrandt and White) were examined and identified. A basal MS medium exhibited the highest 9-methoxycanthin- 6-one content (3.84 mglg DW tissues). Hence, MS medium was selected for subsequent studies. The study on the effect of MS medium strenght (quarter, half, full and double strength) on 9-methoxycanthin-6-one production showed that for full strength of MS, 4.97 mg of the compound per DW tissues could be obtained from callus cultured in quarter MS basal media. The effects of five different carbon sources such as sucrose, glucose, fructose, sorbitol and mannitol [(O, 1.0, 2.0, 3.0, 4.0 and 5.0 % (wlv)] on 9-methoxycanthin-6-one production were studied separately. Two % (w/v) fructose promoted the production of 9-methoxycanthin-6-one (4.59 mglg DW) and gained the highest yield compared to other carbon sources tested. A series of studies was also carried out to examine the effects of various concentrations [(O, 1.0, 2.0, 3.0, 4.0 and 5.0 mg/L in full strength MS medium supplemented with 3 % (w/v) sucrose)] of PGRs (plant growth regulators auxins) (2,4-D, picloram, dicamba, NAA and IAA) on callus growth and 9-methoxycanthin-6-one production. The addition of 3.0 mg/L dicamba increased the 9-methoxycanthin-6-one production (12.3 mglg DW tissues). The effects of different initial pH values (5.0, 5.5, 6.0, 6.5, 7.0, 7.5 and 8.0) on growth and 9-methoxycanthin-6-one production of Eurycoma Iongifolia Jack callus cultures was observed. The highest 9-methoxycanthin-6-one production was obtained at pH 5.5 (1.53 mglg DW tissues). Feeding of each amino acids (DL-tryptophan, L-phenylalanine and L-tryrosine) at a series of concentrations (0, 1x10-~1, x10"~1 x1o - ~l,x lo', 1. O, 1x1o ', 1x1o *, 1x103, 1x10~ pM) was observed to reduce the callus biomass growth as well as the 9-methoxycanthin- 6-one production. The production of 9-methoxycanthin-6-one (2.34 mg/g DW tissues) in callus cultures also increased when the medium was supplemented with 1x10" pM phenylalanine.